Faculdade Aberta para a Terceira Idade FEFISO/ACM de Sorocaba: educação para o envelhecimento e seus efeitos nos participantes - Corvino, Evandro Diniz (2010)
This research aims to show the effects of the Open College for Seniors, College of Physical Education FEFISO/ACM Sorocaba /SP (FAATI/FEFISOACM) to improve health, functional capacity, quality of life and independence of participants. This is a survey of 73 women, aged between 52 and 88 years, attending FAATI only once a week, for two hours. Regardless of education level, there was no difficulty in answering the questions. The participants underwent a battery of questionnaires before and after participating in FAATI for a year. 10 teachers who were involved in this one year of teaching were also evaluated. This data collection of teachers was aimed at the qualification perceived by teachers for each of the aspects investigated. Five questionnaires were applied (1-Assessment of quality of life, 2- Evaluation of Depression Level, 3-Evaluation of Intelligent Eating, 4- Scale of Self-Perception of Wellness and 5-Scale of Self-Assessment of Functional Capacity). After this study it appears that, with regard to age groups, we found that the most represented age group is 65-74 years, a total of 46.5%. The results showed meaningful satisfactory rates between assessment and reassessment in the Quality of Life in the levels of humor, Food Quality, Scale of Self-Perception of Wellness and Functional Capacity. It is concluded that FAATI had positive results for improving health, functional capacity, quality of life and independence of participants